Identifikasi Konfigurasi Struktur Geologi Bawah Permukaan Berdasarkan Data Anomali Medan Gravitasi dengan Teknik Deteksi Tepi dan Dekonvolusi Euler di Daerah Panas Bumi Lainea - Nursinta Atsaniyah Misquita; Jamhir Safani; Al Rubaiyn (Program Studi Teknik Geofisika FITK UHO, 2024)
this research is located in Lainea District, Lainea Village, Southeast Sulawesi, which aims to determine the subsurface structure based on the edge detection technique and determine the depth of the anomaly source using euler deconvolution. Fault segmentation with varying trends and depths illustrates the complexity of tectonic activity around the research area. The application of several edge detection techniques to the residual anomaly data shows the superiority of the TAHG approach in identifying the edges of geothermal source zones and the alignment of geological structures while the TDX approach only shows the boundaries of the anomalies. The euler deconvolution depth solution shows that the faults generated from the TAHG approach belong to shallow faults.